Using Wordscapes Game as a Tool to Develop EFL Learners’ Vocabulary Repertoire (Journal of the College of Basic Education, 2019)
The most vital part of our lives nowadays is technology. It has changed our lives in many ways. It makes life well-situated for us. At the present time, young people are more expected to be seen playing video games. Some assume that movies, TV, and video games are a bad influence on kids, and they hold responsible on these media for causing different problems. Supposed negative effects such as addiction, increased aggression, and various health consequences such as obesity and repetitive strain injuries tend to get far more media coverage than the positives. While there are some negatives on playing video games, there’s no denying that they stop us from getting outside. There are also some benefits. Surprisingly, playing video games can help our physical, mental, and emotional health. A growing number of researchers believed that if used in the right way, video and computer games have the potential to inspire learning. And they can help players improve organization and visual skills. Thus, when learning is channeled into an enjoyable game, they are very often willing to invest considerable time and effort in playing it. Moreover, in view of diverse learning styles and preferences the students display, benefits from games seem to cater for everyone as learners find playing activities much richer language studying work than doing other kinds of practice. If games are properly designed, they may become an excellent and essential part of a learners’ learning programme. On the other hand, it is noteworthy that games like any other activity or tool can be overused when exploited too much so that the motivating element disappears rapidly. ABSTRACTPlaying games such as puzzle games, word search, crosswords, mix and matching, scrabble, etc. are brain motivating problems that test one’s creativity. These games increase brain power which makes them a proper choice for use in educational purposes besides just providing mere entertainment. They educate, improve your intelligence proportion, improve your cognitive ability, improve your concentration, develop motor skills, improve your problem solving skills, improve productivity and can improve your social skills.The most preferred game at the moment is the game developed by People Fun! named “WordScapes”. The game starts with easy puzzles and becomes challenging. There are over 800 puzzles in this game which is really astonishing. Despite the fact that, the developers call it up-to-the-minute word game, it’s quite regular word games. In addition, not too much only one of its kind like Alpha Swipe or Under a Spell. But, it’s really pleasurable and one of the most addicting word puzzle game.In addition to the distraction significance of games, they have great didactic latent. Games exclusively intended to deal with a specific problem such as developing learners’ vocabulary repertoire or teach a specific skill have been very successful, in particular because they are motivating, engaging, interactive, and provide rewards and strengthening to improve.